A OPTIMALISASI PENINGKATAN BERAT BADAN PADA BALITA - Iftita Laistania; Arum Meiranny (JURNAL KEBIDANAN BESTARI, 2025)
Underweight is one of the cases in Indonesia, which is 17% of the most common problems. Underweight conditions in children under five years old are more dangerous, but are usually not directly related to family nutritional problems. Low birth weight (LBW) is one of the causes of underweight in children under five years old. The aim is to see how to deal with underweight in toddlers. This article was written using the literature review method with a literature review taken from health journal databases such as Google Scholar and Pubmed; articles selected based on full text, free open access, and in English and Indonesian. The results show that treatment and prevention of underweight are very important for toddlers.